Three-dimensional color code thresholds via statistical-mechanical mapping - Svore, Krysta M.; Beverland, Michael (2017)
Three-dimensional (3D) color codes have advantages for fault-tolerant quantum computing, such as protected quantum gates with relatively low overhead and robustness against imperfect mea- surement of error syndromes. Here we investigate the storage threshold error rates for bit- ip and phase- ip noise in the 3D color code on the body-centererd cubic lattice, assuming perfect syndrome measurements. In particular, by exploiting a connection between error correction and statistical mechanics, we estimate the threshold for 1D string-like and 2D sheet-like logical operators to be p(1) 3DCC ' 1:9% and p(2) 3DCC ' 27:6%. We obtain these results by using parallel tempering Monte Carlo simulations to study the disorder-temperature phase diagrams of two new 3D statistical-mechanical models: the 4- and 6-body random coupling Ising models.